The Association of Hospitalization with Parenting Stress and Quality of Life in Parents of Children with Thalassemia - Fadila Rahmawati; Titi Pambudi Kurniawaty; Yudhi Kurniawan; Agustine Mahardika (Faculty of Medicine, Universitas Tadulako, 2026)
Background: Children with thalassemia require repeated hospital attendance for transfusion and related care, which may contribute to parental stress and quality-of-life burden. Objectives: This study aimed to assess the association of hospitalization-related attendance with parenting stress and parental quality of life. Methods: This cross-sectional study included 35 parents of children with thalassemia at the NTB Provincial General Hospital. Parenting stress and quality of life were assessed using the PSI-SF and WHOQOL-BREF. Hospital attendance duration, frequency, and interval were analyzed using Spearman, chi-square, and Fisher’s exact tests as appropriate. Results: Low parenting stress was reported by 68.6% of parents and very good quality of life by 88.6%. No statistically significant association was detected between hospital attendance duration, frequency, or interval and parenting stress (p=0.606, 0.884, and 0.121) or quality of life (p=0.951, 0.359, and 0.726). Splenomegaly was associated with parenting stress (p=0.020), and parental age was associated with quality of life (p=0.009). Conclusion: In this small cross-sectional sample, hospitalization-related attendance parameters were not significantly associated with parenting stress or parental quality of life; the findings should be interpreted cautiously because of limited statistical power.